Artificial Intelligence-Based Research Trends and Literacy Shifts in Linguistics and Literature Journals: A Systematic Literature Review - Rendy Pribadi; Yulian Dinihari; Rina Rosdiana; Ajeng Dinar Wisesa Wardhani (Raja Zulkarnain Education Foundation, 2025)
This study aims to map trends in artificial intelligence-based research in linguistics and literature journals in Indonesia and to map the shifts in academic literacy that have emerged due to the use of artificial intelligence technology. The method used is a Systematic Literature Review (SLR). The research sample comprises 67 articles from 40 journals, indexed by Sinta 1–5, for the period 2020–2025. Data were collected using document and observation techniques. The analysis focused on four main aspects: research subjects, research types, the type of artificial intelligence used, and data collection techniques, the most prominent of which are document and questionnaire techniques. The results of the study indicate that trends in AI-based linguistics and literature research in Indonesia are dominated by university- and student-led qualitative research. The most commonly used types of artificial intelligence are ChatGPT, Grammarly, and Elsa Speak. Data collection methods include surveys, tests, and questionnaires. However, shifts in academic literacy are also occurring, requiring strengthening reading and writing literacy so that the use of artificial intelligence remains ethical, reflective, and supports the sustainable development of linguistics and literature.